STATINS IN PREVENTION OF ISCHEMIC STROKE - A. V. Susekov; A. B. Blohin; Z. G. Luginova; E. J. Soloveva; N. V. Maltseva; O. E. Tarasova; V. V. Kuharchuk (Столичная издательская компания, 2015)
The evidence base of statin therapy in primary and secondary prevention of ischemic stroke is surveyed. Results of classical trails with statins in ischemic stroke prevention as well as results of meta-analyses are discussed.